Psychiatric manifestations in ulcerative colitis: a North Indian cohort study - Singh, Kuldeep; Choudhary, Swati (International Journal of Research in Medical Sciences, 2025)
Background: Ulcerative colitis (UC) is a chronic inflammatory bowel disease that causes results in gastrointestinal and other health issues. Psychiatric problems are being recognized more often but are still often missed, particularly in India. Aim of the study was to examine the demographics, disease characteristics, and psychiatric symptoms of UC patients in North India. Methods: A prospective observational study of 100 UC patients was carried out from September 2021 to September 2023. Demographics, disease extent, severity, and psychiatric outcomes were recorded, and all patients were assessed for depression and anxiety using PHQ-9 and GAD-7 scores. Results: The mean age of the study cohort was 38.6±12.4 yrs, with 58% being male. Pancolitis was found in 48% of the patients. Clinically significant depression (PHQ-9 ≥10) and anxiety (GAD-7 ≥10) were seen in 28% and 26%, respectively. Sleep disturbances affected 44% of the patients, and fatigue was reported by 47%. Steroid-related psychiatric events occurred in 3%. Conclusions: Psychiatric symptoms are common in UC and can negatively impact quality of life. Comprehensive care requires regular screening and a team-based approach.